At the Interface of Lifestyle, Behavior, and Circadian Rhythms: Metabolic Implications - Bae, Seul-A; Fang, Ming Zhu; Rustgi, Vinod; Zarbl, Helmut; Androulakis, Ioannis P. (Frontiers in Nutrition, 2019)
Nutrient metabolism is under circadian regulation. Disruption of circadian rhythms by stressors, lifestyle and behavioral choices such as work schedules, eating patterns and jetlag, including social, seriously impact and impair metabolism. Metabolic dysfunction due to chronic misalignment of the organism’s endogenous rhythms and environmental cues is detrimental to health, increasing the risk of obesity, metabolic and cardiovascular disease, diabetes and cancer. In this paper, we review literature on recent findings on the mechanisms that communicate metabolic signals to circadian clocks, and how human behavioral changes imposed by social and occupational demands affect the known components of the network integrating peripheral clocks and metabolism. We also discuss possible factors that contribute to inter-individual variability in response to circadian changes in the context of metabolic function.